Singapore Ocular Tuberculosis Immunity Study (SPOTIS): Role of T-lymphocyte profiling in patients with presumed ocular tuberculosis - Paul Hutchinson (Taylor & Francis, 2022)
10.1080/09273948.2020.1767791